2023
DOI: 10.20944/preprints202307.1906.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurocognitive Profile of Creativity in Improving Academic Performance. A Scoping Review

Maria Tzachrista,
Evgenia Gkintoni,
Constantinos Halkiopoulos

Abstract: Academic performance and capabilities were greatly influenced by creativity. It has also contributed to comprehending academic skill development independent of motivation and intelligence. This study examines the relationship between student creativity and academic skills. This is the systematic literature review for 2016 to 2022. The main criteria for including an article in the research were that it was written in English, that it was pertinent to the topic of the study, that its sample consisted of students… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…However, a modest correlation is observed solely concerning two specific aspects of emotional intelligence: emotion appraisal and emotion regulation. As anticipated, educators from diverse nations and disciplines exhibit elevated levels of emotional intelligence, resulting in enhanced efficacy in classroom management, conflict resolution, and the regulation of students' emotional well-being (Tzachrista et al, 2023). The findings also indicate that physicians working in public hospitals demonstrate significantly higher levels of emotional intelligence compared to those in private hospitals, showcasing enhanced self-awareness, social empathic abilities, and trust.…”
Section: Resultssupporting
confidence: 53%
“…However, a modest correlation is observed solely concerning two specific aspects of emotional intelligence: emotion appraisal and emotion regulation. As anticipated, educators from diverse nations and disciplines exhibit elevated levels of emotional intelligence, resulting in enhanced efficacy in classroom management, conflict resolution, and the regulation of students' emotional well-being (Tzachrista et al, 2023). The findings also indicate that physicians working in public hospitals demonstrate significantly higher levels of emotional intelligence compared to those in private hospitals, showcasing enhanced self-awareness, social empathic abilities, and trust.…”
Section: Resultssupporting
confidence: 53%
“…However, it was found that conscientiousness did not significantly impact the ratings. Notably, non-cooperation, or discordance, constitutes a fundamental component of creativity (Tzachrista et al, 2023). Nonconformists are often perceived as individuals with a propensity for creativity and achievement.…”
Section: Resultsmentioning
confidence: 99%
“…Employees' personality traits play a crucial role in determining their job performance and overall job satisfaction. Specific characteristics have been found to positively impact performance, such as extroversion, conscientiousness, openness to experience, and friendliness (Tzachrista et al, 2023). On the other hand, certain traits have been found to have a negative effect on performance, such as toxicity and neuroticism.…”
Section: Discussionmentioning
confidence: 99%
“…These traits have been observed to change over time, with extroversion and conscientiousness decreasing while self-confidence increases (Antonopoulou et al, 2023). The concept of receptivity to experience is closely linked to effective leadership, as it is associated with the ability to think divergently, generate original ideas, and exhibit creativity (Sortwell et al, 2023;Tzachrista et al, 2023). This trait is commonly observed in individuals with elevated levels of receptivity to experience (Singh & Pathardikar, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%